1995
DOI: 10.2307/3578966
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Effectiveness of Radon-Progeny Alpha Particles. II. Oncogenic Transformation as a Function of Linear Energy Transfer

Abstract: Epidemiological studies have established an association between exposure to radon and carcinoma of the lung. However, based on data for either lung cancer in uranium miners exposed to radon or bronchial epithelial carcinomas in Japanese A-bomb survivors, it has not been possible to assign estimates of risk of lung cancer for the general population exposed to radon in their homes. Based on past success with the excellent quantitative properties of the C3H 10T1/2 in vitro oncogenic transformation assay system, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 15 publications
0
77
0
Order By: Relevance
“…Based on the extensive studies of in vitro alpha particle cellular dose response to ionizing radiations (Miller et al 1995, 1999, Zhou et al 2001, 2004, Nagasawa and Little 1999, 2002, Nagasawa et al 2003, Hei et al 1997, Sawant et al 2001 and analyzed in Part I, there has been a presumption that the Bystander Effect is experienced by humans in the induction of radon induced lung cancer (Zhou et al 2001, Brenner and Sachs 2002, Little and Wakeford 2001, Little 2004). The extensive Adaptive Response in vitro research cited here (Azzam et al 1996, Elmore et al 2006, Ko et al 2004, Redpath et al 2001, Redpath and Antoniono 1998, Shadley and Wiencke 1989, Wiencke et al 1986, Wolff et al 1989 and analyzed with the composite AR and BE Microdose Model (Leonard 2005, 2008a, 2008b) is supportive of humans experiencing Adaptive Response radio-protection from low LET radiation exposures.…”
Section: B E Leonard and Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the extensive studies of in vitro alpha particle cellular dose response to ionizing radiations (Miller et al 1995, 1999, Zhou et al 2001, 2004, Nagasawa and Little 1999, 2002, Nagasawa et al 2003, Hei et al 1997, Sawant et al 2001 and analyzed in Part I, there has been a presumption that the Bystander Effect is experienced by humans in the induction of radon induced lung cancer (Zhou et al 2001, Brenner and Sachs 2002, Little and Wakeford 2001, Little 2004). The extensive Adaptive Response in vitro research cited here (Azzam et al 1996, Elmore et al 2006, Ko et al 2004, Redpath et al 2001, Redpath and Antoniono 1998, Shadley and Wiencke 1989, Wiencke et al 1986, Wolff et al 1989 and analyzed with the composite AR and BE Microdose Model (Leonard 2005, 2008a, 2008b) is supportive of humans experiencing Adaptive Response radio-protection from low LET radiation exposures.…”
Section: B E Leonard and Othersmentioning
confidence: 99%
“…Neither alpha particle bystander nor low LET adaptive response or combined in vitro experiments have been conducted, to a reasonable extent, directly with the basal and secretory lung cells. The alpha particle LET and RBE broadbeam in vitro experiments of Miller et al (1995) need to be repeated with immortalized basal and secretory cells. Similarly, the low LET adaptive response experiments of Dr. Redpaths group need to be repeated with the immortalized basal and secretory cells.…”
Section: B E Leonard and Othersmentioning
confidence: 99%
“…The modified BaD Model best fit to the Miller et al (1995) exposure of C3H 10T1/2 cells to alpha particles of indicated range of LETs. Experiments are described in Section 3.1.e and 4.1.c and best fit parameters are given in Table 1. Damage Region and the Direct Damage Region, along with the RBE values reported by Miller et al (1995) in their Figure 3. We show a significant difference between the Bystander and Direct Damage values and between these and the Miller et al (1995) values.…”
mentioning
confidence: 99%
“…Briefly, the mean testicular absorbed dose D is given by (26) (2) where the cumulated activity à is the time integral of the activity in the organ ∫A(t)dt, Δ is the mean energy emitted per nuclear transition, φ is the absorbed fraction, m is the average mass of the testis (0.1 g), and i denotes the ith radiation component emitted by the radionuclide. In keeping with our dosimetry procedures for an optimal assay day of 36 days after injection, the cumulated activity was integrated over 13 days (8,11).…”
Section: Testicular Dosimetry and Dose-response Relationship For 148 Gdmentioning
confidence: 99%
“…For in vitro studies, the RBE is strongly dependent on LET with a maximum at about 120 keV/μm. Similarly, Miller et al (2) have investigated oncogenic transformation as a function of LET in cultured C3H 10T1/2 cells and found that the RBE for stochastic effects (RBE M ) is also maximum at about 120 keV/μm. Although there is a relative abundance of such data obtained in vitro, there are few studies investigating the relationship between RBE and LET in vivo.…”
Section: Introductionmentioning
confidence: 99%